Spatio-temporal metrics that distinguish outcomes of field hockey plays - McInerney, C.; Foster, L.; Choppin, S.; Stone, J. (World Congress of Performance Analysis of Sport XI - Alicante, 16th - 18th November 2016, 2016)
Video ab 3:42:24